Effects of Marketing Practices on Farmers Profit in Northern Bangladesh - Haque, Md. Ziaul (Asian Business Review, 2022)
Agriculture is the main foundation of the economy of Bangladesh. This sector contributes about 17.22% to the country's GDP and accommodates around 45.6% of the labor force. New technologies have increased over the past few decades in Bangladesh's agriculture. As a result, agricultural production in the country has grown tremendously, but due to an inefficient marketing system, farmers do not receive the advantage of the enormous output. Because of some inefficiency in the agricultural marketing system, farmers are deprived of the fair price of their produce. Several factors influence the price received by the farmers for their agricultural commodities. This study thus aims to examine marketing practice and the degree of influence of these practices on farmers' profit in Northern Bangladesh. Two districts, namely Naogaon and Dinajpur, were selected purposively from two divisions in Northern Bangladesh. Two upazillas and two villages were chosen following a simple random sampling (SRS) method for collecting data. The study used a set of questionnaires with five sections to collect data. To serve research objectives, 216 farmers were interviewed using a structured questionnaire with a face-to-face interview, and 32 key informant respondents were interviewed using a checklist. To achieve the goal, a multiple linear regression model was used, considering the farmer's profit as a dependent variable, marketing practices as an independent variable, and financial factors as an independent variable. The multiple linear regression model was estimated. The study found that almost cent percent of farmers sell their produce from farmhouses or to the rural Hat at Bepari. It was found that different types of intermediaries were functioning in agricultural marketing: farmers, Farias, Beparies, Aratders, wholesalers, Millers, cold storage owners, and retailers. Using a multiple linear regression model, it was found that three explanatory variables, i.e., the Sale of an agricultural commodity at a town market, Crop storage status, sell produce to public procurement, positively affects the farmer's profit. The remaining two explanatory variables, i.e., the Sale of agricultural commodities during the harvesting period and receiving a loan from informal sources, negatively affect the farmer's profit. Only one independent variable, i.e., Crop storing status, is a statistically insignificant factor. The rest of the four independent variables are statistically significant factors affecting farmers' profit in Northern Bangladesh.
Keywords: Farmers Profit; GDP; Agricultural Production; Agricultural Marketing Systems; Farmhouse